Particularities of the amplitude-time structure of the hindrances in the acoustic sounding system of the atmosphere - Семенец, В.В.; Леонидов, В.И. (Radiotekhnika, 2019)
Acoustic interference is the main factor limiting the functional reliability of the systems of acoustic sounding of the atmosphere. The time frequency acoustic interference structure essentially depends on the location of the acoustic system. The case of the occurrence of combinational noise, generated by complex mechanical systems or systems complexes is the most difficult one. The hypothesis that the time-frequency structure of complex interference is created by some finite set of sources of forcing (main) oscillatory processes, for example, rotation of electric motors, and forced oscillations, caused by the resonant properties of structural elements, is put forward and confirmed. It follows from this that the frequencies of the combinational and fundamental harmonics have a functional dependence, and the forced oscillations have an amplitude dependence on the frequency of the forcing oscillation, while the frequency of the forcing oscillation under the conditions of the functioning of the system varies randomly. It follows from this that with an increase in the duration of the analyzed sample, its amplitude-frequency spectrum approaches a continuous shape. Consequently, the rules for detecting signals based on frequency selection are not effective for the type of interference under consideration. The paper presents the results of the analysis of a different approach to the analysis of combinational noise, based on a temporal analysis of the spectrograms of the periods of the process under study, which, as shown, has a discrete appearance, which creates the necessary theoretical basis for designing and optimizing an adaptive signal detection system under conditions of combination acoustic noise.